Problems of toponym formation methods. (Eurasian Journal of Philology Science and Education, 2015)
The article discusses the methods of word-formation of the Kazakh language, their terms of compliance. It also refers to the principles of word formation that has long existed and their terms are not formed. In our language place names belong to word formation methods. They were formed as a result ofword-formation process. Therefore, the toponym formation methods being the object of research have a significant place in the word-formation system.
Keywords: toponym; toponym formation; word formation; Kazakh language; methods of word formation; complex toponyms